Unravelling the Molecular Mechanisms of a Quercetin Nanocrystal for Treating Potential Parkinson’s Disease in a Rotenone Model: Supporting Evidence of Network Pharmacology and In Silico Data Analysis - Yeruva Sai Lakshmi; D. S. N. B. K. Prasanth; Karumuri Taraka Sunil Kumar; Sheikh F. Ahmad; Seemaladinne Ramanjaneyulu; Nalluri Rahul; Praveen Kumar Pasala (Biomedicines, 2023)
The prevalence of Parkinson’s disease places a significant burden on society; therefore, there is an urgent need to develop more effective drugs. However, the development of these drugs is both expensive and risky. Quercetin (QUE) has potent pharmacological effects on neurodegenerative diseases, but its low solubility in water and poor bioavailability limit its use in pharmaceutical applications. In this study, Quercetin nanocrystals (QNC) were synthesized and compared to standard QUE. A network-pharmacology-based methodology was applied, including target prediction, network construction, a gene ontology (GO) analysis, a KEGG pathway enrichment analysis, and molecular docking. This study aimed to identify the targets of QUE relevant to the treatment of Parkinson’s disease and investigate the associated pharmacological mechanisms. Most of the predicted targets are involved in dopamine uptake during synaptic transmission. QUE regulates the key targets DRD2 and DRD4, which significantly affect dopaminergic synapses. The molecular docking results showed that QUE had a better binding affinity than the standard drug l-Dopa. From these experiments, it can be concluded that QNC effectively reduced the adverse effects caused by rotenone-induced oxidative stress in biochemical, neurochemical, and histopathological alterations. Therefore, QNC can potentially treat Parkinson’s disease, and its effectiveness should be assessed in future clinical trials.